“The oversensitive, demanding parent” vs. “the professional teacher”- the ongoing struggle for the common ground of parent-teacher collaboration in Poland - Rusnak, Monika (International Journal about Parents in Education, 2023)
The starting point for this article is the contradiction between research results and policy recommendations on the one hand and the school reality of collaboration between teachers and parents on the other one. My point is to underline the importance of parent-teacher cooperation and obstacles preventing it in everyday school life in Poland. Notwithstanding the obvious benefits of such collaboration, this area seems still to be neglected in the majority of Polish schools. In the article I will comment on the results of research conducted in Poland in recent years, which testifies to the discrepancies between the theory and practice. I will also share the results of my own qualitative action research, in which I work to overcome the existing boundaries – the resistance of teachers and schools towards parents on the one hand, and a lack of involvement of parents on the other.